A Leaf Disease Detection Mechanism Based on L1-Norm Minimization Extreme Learning Machine - Dwivedi R.; Dutta T.; Hu Y.-C. (My University, 2025)
The disease-free growth of a plant is highly influential for both environment and human life, as numerous microorganisms/viruses/fungus may affect the growth and agricultural production of a plant. Early detection and treatment thus becomes necessary and must be treated on time. The existing vision techniques either involve image segmentation or feature classification/regression applied over aerial images. This results in an increase in time and cost consumption due to various challenges, such as generalization ability and learning cost. Therefore, a feature-based disease detection approach with minimal learning time and generalization ability could be fairly befitting such as an extreme learning machine (ELM). In this letter, we demonstrate an algorithm, L1-ELM, after employing Kuan filtering for preprocessing and different feature computations. At the evaluation stage, the experimentation performed over benchmark plant datasets confirms that L1-ELM outperforms all existing one-class classification algorithms, preserving optimal learning and better generalization. © 2004-2012 IEEE.